AYUSH- 64: A potential therapeutic agent in COVID-19 - Ashok Kumar Panda; Sarbeswar Kar; Amit Kumar Rai; B.C.S. Rao; N. Srikanth (Journal of Ayurveda and Integrative Medicine, 2022)
Corona Virus disease (COVID-19) has become a global pandemic resulting in large scale morbidity and mortality worldwide. The management of COVID-19 has been a big challenge because of multifactorial pathophysiology and no specific treatment. AYUSH-64, a poly-herbal formulation developed by CCRAS, Ministry of AYUSH, Govt. of India through extensive pharmacological, toxicological and clinical studies has proven its safety and efficacy in infective febrile conditions such as malaria and influenza. AYUSH- 64 has four ingredients having immunomodulatory, anti-inflammatory, antipyretic, antioxidant and anti-viral activities. It arrests the extreme inflammatory responses in COVID-19 that causes progression to significant morbidity. AYUSH-64 has also been incorporated in the National COVID management protocol based on Ayurveda and Yoga by Government of India for asymptomatic and mild cases of COVID-19. Further, on the basis of tangible evidence generated through robust clinical and experimental studies on AYUSH-64, the Ministry of AYUSH has launched nation-wide campaign for mass distribution of AYUSH-64 to asymptomatic, mild to moderate COVID-19 patients in home isolation to reduce the burden on the hospital. This review will highlight the specifications of AYUSH-64, its mechanism of action, its repurposing for COVID-19, various clinical and experimental studies.